2014
DOI: 10.4187/respcare.03084
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Risk in Subjects With Asthma With or Without Comorbid Rhinitis

Abstract: BACKGROUND: As many as 80% of patients with asthma suffer from allergic rhinitis (AR), and rhinitis symptoms are associated with sleep complaints The aim of this cross-sectional study was to assess the prevalence of obstructive sleep apnea syndrome risk in patients with asthma and to explore the association between comorbid rhinitis and obstructive sleep apnea syndrome risk. METHODS: Subjects with asthma were recruited by general practitioners during a control visit. Physicians compiled a questionnaire that as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…First, shared risks and comorbid conditions, such as GERD, rhinitis, and obesity, could play a very important role [1316]. For example, Braido F et al reported that 52.6% (1021/1941) of asthma subjects had OSA, including 47.3% (350/740) with asthma alone and 55.9% (671/1201) with asthma and allergic rhinitis [16]. In the present study, we also noticed strong combined effects of these comorbidities and asthma on the risk of OSA, particularly those with GERD (adjusted HR: 11.4) and with obesity (adjusted HR: 6.07).…”
Section: Discussionmentioning
confidence: 99%
“…First, shared risks and comorbid conditions, such as GERD, rhinitis, and obesity, could play a very important role [1316]. For example, Braido F et al reported that 52.6% (1021/1941) of asthma subjects had OSA, including 47.3% (350/740) with asthma alone and 55.9% (671/1201) with asthma and allergic rhinitis [16]. In the present study, we also noticed strong combined effects of these comorbidities and asthma on the risk of OSA, particularly those with GERD (adjusted HR: 11.4) and with obesity (adjusted HR: 6.07).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that snoring was associated with local airway symptoms, such as wheezing and expectoration. The airway runs from the nose, through the throat, trachea and bronchus to the bronchioles, and each part of this structure has associated airway disorders, such as sinusitis/rhinitis, asthma and OSA, [16][17][18][19][20] giving rise to the concepts of "one airway, one disease", 21 "the atopic march", 17 and "the overlap syndrome of asthma and OSA". 22,23 These concepts were confirmed by various epidemiological studies, such as the Wisconsin Sleep Cohort Study.…”
Section: Discussionmentioning
confidence: 99%
“…Both allergic and nonallergic rhinitis are independent risk factors for obstructive sleep apnoea, likely related to nasal congestion and reduced upper airway patency (Figure ) …”
Section: To What Degree Do Comorbidities Contribute To Difficult Asthma?mentioning
confidence: 99%